ANALISIS UJARAN KEBENCIAN TERHADAP PENGGUNAAN KECERDASAN BUATAN DAN DAMPAKNYA TERHADAP PERSEPSI MASYARAKAT DI PLATFORM X: KAJIAN TINDAK TUTUR ILOKUSI DAN PERLOKUSI - Kistosi Al Ghifari; Pradana Yahya Abdillah; Tanaya Edra Abitama; Muhammad Rizqon Karim; Fahmilatul Khairunnafisah; Siti Maesaroh (CV. Denasya Smart Publisher, 2026)
The rapid development of artificial intelligence (AI) in Indonesia has sparked diverse public reactions on social media, with some expressions degenerating into hate speech beyond constructive criticism. This study aims to identify and classify forms of hate speech against the use of AI on platform X (Twitter) and to analyze its perlocutionary impact on public perception of the technology. A descriptive-qualitative approach based on Searle's speech act theory is employed, focusing on illocutionary classification and the analysis of perlocutionary impact, with the locutionary level serving as a contextual framework. Data were collected through a targeted sampling of 37 posts on X containing negative reactions to the use of AI, gathered between 2023 and 2026. The analysis shows that hate speech against AI manifests itself in five illocutionary categories: assertive (40%), expressive (28%), directive (36%), commissive (20%), and declarative (24%), with directive and assertive acts being the most frequent. The identified perlocutionary effects include the reinforcement of fear-based narratives about AI, the emergence of social polarization between AI users and opponents, and pressure to conform in the digital sphere. These findings suggest that hate speech against AI is not merely an expression of individual dissatisfaction but a discursive practice that shapes the collective perception of technology. This research contributes to the development of frameworks for digital literacy and AI governance policies in Indonesia by providing a pragmatic-linguistic perspective that has been largely absent from previous sentiment-based research